Competitive Strategy Analysis for Digital Products on Kompas Daily - Nur Rahmawati; Krisna, Paula (JURNAL ADMINISTRASI BISNIS (JAB), 2023)
This study aims to analyze and identify the key success factors in the industry and its competition, analyze and identify competitive advantages of Kompas digital products, and formulate competitive strategies for Kompas digital products. This research is qualitative descriptive, by analyzing the company’s external environment using macro-PESTEL environmental analysis, the industry analysis using Five Forces Porter, and the analysis using the key success factors. The value chain analysis and VRIO-competitive advantage analyze the internal environment of the company. The results of this study indicate that the strategy applied by Kompas is a product differentiation strategy because this strategy is considered to be the most appropriate to the conditions of the company. Differentiation strategies are carried out by the companies to get uniqueness towards competitors.